Diagnostics of multicomponent electric arc plasma - Cheredarchuk, A.I.; Boretskij, V.F.; Veklich, A.N. (Вопросы атомной науки и техники, 2011)
The plasma parameters of electric arc discharge in a gas flow between copper electrodes were investigated. The
electrical conductivity of copper-argon and copper-carbon dioxide plasma was calculated. It was found that at low
temperatures (5000 K<T<9000 K) the electrical conductivity considerably depends on the amount of copper in plasma. Досліджувалися параметри плазми електродугового розряду у потоці газу між мідними електродами.
Розраховано електропровідність плазми мідь-аргон та мідь-вуглекислий газ. Встановлено, що при низьких
температурах (5000 K < T < 9000 K) електропровідність суттєво залежить від кількості міді в плазмі. Исследовались параметры плазмы электродугового разряда в потоке газа между медными электродами.
Рассчитана электропроводность плазмы медь-аргон и медь-углекислый газ. Установлено, что при низких
температурах (5000 K < T < 9000 K) электропроводность существенно зависит от количества меди в плазме.